Penerapan Hukum Kekayaan Intelektual terhadap Sengketa Kasus Merek Geprek Bensu Menggunakan UU No 20 Tahun 2016 (International Forum of Researchers and Lecturers, 2024)
The rise of trademark and copyright issues in Indonesia is related to the reality of globalization in modern trade, because inventive progress often causes plagiarism difficulties and challenges the legal framework of modern intellectual property rights. In the case of Ruben Onsu and Geprek Bensu, this journal attempts to answer several issues from the problem. The research method used is juridical-normative with a qualitative approach to explore data and analyze related legal norms. This study explores copyright protection in the culinary industry, the tension between name ownership and trademark rights. This journal will focus on the urgency of trademark registration and how to resolve the Geprek Bensu dispute.